Predictors of Outcome following Stroke due to Isolated M2 Occlusions - Khan, Muhib (S. Karger AG, 2014)
BACKGROUND: Factors influencing outcome after cerebral artery occlusion are not completely understood. Although it is well accepted that the site of arterial occlusion critically influences outcome, the majority of studies investigating this issue has focused on proximal large artery occlusion. To gain a better understanding of factors influencing outcome after distal large artery occlusion, we sought to assess predictors of outcome following isolated M2 middle cerebral artery occlusion infarcts. METHODS: We retrospectively analyzed patients with isolated acute M2 occlusion admitted to a single academic center from January 2010 to August 2012. Baseline clinical, laboratory imaging, and outcome data were assessed from a prospectively collected database. Factors associated with a modified Rankin Scale (mRS) score ≤2 in univariable analyses (p < 0.05) were entered into multivariable logistic regression analysis. The Admission National Institutes of Health Stroke Scale (aNIHSS) score, age, and infarct volume were also entered as dichotomized variables. Receiver operating characteristic curves were plotted to determine the optimal aNIHSS score, infarct volume, and age cut points predicting an mRS score ≤2. Optimal thresholds were determined by maximizing the Youden index. Respective multivariable logistic regression analyses were used to identify independent predictors of a good 90-day outcome (mRS score ≤2; primary analysis) as well as 90-day mortality (secondary outcome). RESULTS: 90 patients with isolated M2 occlusion were included in the final analyses. Of these, 69% had a good 90-day outcome which was associated with age <80 years (p = 0.007), aNIHSS <10 (p = 0.002), and infarct volume ≤26 ml (p < 0.001). Notably, 20% of patients (64% of those with a poor outcome) had died by 90 days. Secondary analysis for 90-day mortality was performed. This analysis indicated that infarct volume >28 ml (OR 11.874, 95% CI 2.630-53.604, p = 0.001), age >80 years (OR 4.953, 95% CI 1.087-22.563, p = 0.039), need for intubation (OR 7.788, 95% CI 1.072-56.604), and history of congestive heart failure (OR 5.819, 95% CI 1.140-29.695) were independent predictors of 90-day mortality (20% of all included patients). CONCLUSION: While the majority of patients with isolated M2 occlusion stroke has a good 90-day outcome, a substantial proportion of subjects dies by 90 days, as identified by a unique subset of predictors. The knowledge gained from our study may lead to an improvement in the prognostic accuracy, clinical management, and resource utilization in this patient population.